Development of a test bench for biomechanical simulation—a preliminary study of mandibular forces - Ben Achour, Anas; Apfeld, Florian; Lauer, Günter; Bräuer, Christian; Leonhardt, Henry; Franke, Adrian; Lipphaus, Andreas; Teicher, Uwe; Witzel, Ulrich; Schröder, Tom Alexander (Frontiers in Bioengineering and Biotechnology, 2024)
The aim of this study is to develop a test bench, which integrates different complexity levels and enables flexible and dynamic testing for different intervals as well as testing of maximum loads of osteosynthesis systems on the mandible. For this purpose, an analysis of the SoA regarding existing test benches was combined with interviews of clinical experts to acquire a list of requirements. Based on these a design for a modular test bench was developed. During the implementation, functional tests were continuously carried out and improvements made. Depending on the complexity, the test bench can be used either as an incorporated variant or as a standalone solution. In order to verify the performance of these two variants of the test bench, preliminary studies were carried out for all levels of complexity. In these preliminary studies, commercially available osteosynthesis and reconstruction plates were investigated for their biomechanical behaviour and compared with data from the literature. In total, fourteen test runs were performed for the different levels of complexity. Firstly, five test runs were executed to test the simplified load scenario in the incorporated variant of the test bench. High forces could be transmitted without failure of the miniplates. Secondly a quasi-static test scenario was examined using the incorporated variant with simplified load insertion. Five experiments with a number of cycles between 40.896 and 100.000 cycles were carried out. The last four test runs were carried out using the standalone variant of the test bench simulating complex load patterns via the insertion of forces through imitated muscles. During the test runs joint forces were measured and the amplitude and vector of the resulting joint forces were calculated for both temporomandibular joints. Differences in the force transmission depending on the implant system in comparison to the zero sample could be observed.The presented modular test bench showed to be applicable for examination of the biomechanical behavior of the mandible. It is characterized by the adjustability of the complexity regarding the load patterns and enables the subsequent integration of further sensor technologies. Follow-up studies are necessary to further qualify and optimize the test bench.